Teaching STEM in the secondary school : helping teachers meet the challenge - Banks, Frank, 1953-; Barlex, David (New York, NY : Routledge, 2014)
'The skills, knowledge and understanding of the subjects involved in STEM (science, technology, engineering and mathematics) are vital for all young people in an increasingly science and technology driven society. This book looks at the purpose and pedagogy of STEM teaching and explores the ways in which STEM subjects can interact in the curriculum to enhance student understanding, achievement and motivation. By reaching outside their own classroom, teachers can collaborate across subjects to enrich learning and help students relate school science, maths and technology to the wider world. Packed with ideas and practical details for teachers of STEM subjects, this book: Considers what the STEM subjects contribute separately to the curriculum and how they relate to each other in the wider education of secondary school students;Describes and evaluates different curriculum models for STEM;Suggests ways in which a critical approach to the pedagogy of the classroom, laboratory and workshop can support STEM for all students;addresses the practicalities of introducing, organising and sustaining STEM related activities in the secondary school Looks to ways schools can manage and sustain STEM approaches in the long-term. This timely new text is essential reading for trainee and practising teachers that wish to make the learning of science, technology, engineering and mathematics an interesting, motivating and exciting experience for their students.'--
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Secondary); Technology -- Study and teaching (Secondary); Engineering -- Study and teaching (Secondary); Mathematics -- Study and teaching (Secondary)